Predicting Accident Zone in Thanjavur City Using Data Mining Techniques - Sterlin, S; Lakshmi, K (International Journal of Computer Sciences and Engineering, 2025)
The objective of this project is to predict the accident zone in kumbakonam city. This will be very useful to transport department as well as administration department of kumbakonam city and take decision easily about the accident zone. This project will give the references about the accidents places in kumbakonam city. It is very useful to reduce the accidents in the kumbakonam city. This project contains two major modules namely Administrator and User. Both administrator and user may be a police. Administrator must be a higher authority. The privilege of the administrator is to create, update and delete the users’ account. Administrator can view and delete the accident data’s which was updated by the user. Major operation by an administrator is to maintain accident data’s and user data’s. The privilege of the user is to add and update accident data’s. Those accident data’s can be used to generate the report about the accidents happened in kumbakonam city. User can view their profile and also view the accident data